PELAKSANAAN PRINSIP – PRINSIP PELAYANAN PUBLIK DALAM PERSETUJUAN BANGUNAN GEDUNG PADA DPMPTSP KOTA PEKANBARU TAHUN 2023 - ,, Salsabilah; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Public service is the most visible measure of government performance. The public can directly assess a government's performance based on the quality of public services received, as this quality is felt by all levels of society. Success in establishing professional, effective, efficient, and accountable public service performance is crucial. Therefore, the government must adhere to laws and continually strive to improve the quality of public services. The purpose of this study was to determine the implementation of public service principles in building approvals at the Pekanbaru City Public Works and Public Housing Agency (DPMPTSP) in 2023, referring to Mahmudi's (2007) theory of public service principles: procedural simplicity, clarity, timeliness, completeness of facilities and infrastructure, ease of access, and discipline, politeness, and friendliness. This research is a descriptive qualitative study with primary and secondary data sources. Data collection techniques used were interviews and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of this study are that the application of public service principles in PBG in Pekanbaru City has been implemented and the Pekanbaru City government has also begun to improve its services in building permit services, but it has not been running perfectly because there are several indicators that are still difficult for the public to understand and are not implemented properly by the Pekanbaru City DPMPTSP. Keywords: Implementation, Service Principles, and Building Approval